Światowy kryzys finansowy i jego wpływ na turystykę w Polsce - Taraszkiewicz, Tomasz (Short and Long-Term Implications of Financial Crisis and its Influence on Tourism, 2009)
Considering the structure, dynamics and the area of occurrence, the world's financial crisis of 2007-2009 reveals many analogies to the Great Depression in the thirties of the 20th century. With a diverse intensity, various repercussions appear in many branches in different parts of the globe. Help worth billions provided to banking sector has not stopped the crisis from extension. The negative effects have also been noticed in the tourist branch, where in 2009 a short-term l-2%15 decrease is expected in the international tourist traffic.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 859-866